Synthesis, Formation And Characterization Of Nanoscale Zeolite Type W Base Catalyst - Cheong, Ying Wai (2021)
Zeolite W (MER topology) is a very important zeolite in catalysis and separation industries but its synthesis requires the use of organic structure-directing agents (OSDAs) and long crystallization time. This project aims to synthesize and study the formation of nanosized zeolite W without organic structure-directing agent with shortened synthesis time while using it as heterogeneous catalyst for various base-catalyzed organic reactions. The first part focuses on studying the effect of the synthesis parameters such as heating temperature, reaction time and hydrogel chemical compositions on the crystallization behaviour of zeolite W. It is found that the synthesis parameters have significant impact on the crystallization rate, purity of the zeolite phase, particle size and morphology of the zeolite product. By tuning the synthesis parameters, zeolite W with four distinct morphologies (nanorods, wheatsheaf-like, bullet-like and prismatic) can be obtained. Further investigation into the relationship between different morphologies and their surface basicity found that the surface basicity is linearly proportional to the surface area of the zeolites. Next, the time-dependent study on the nucleation and crystal growth process of nanosized zeolite W synthesized with reactive bamboo leaves ash (BLA) was reported. Various spectroscopic, microscopic and analytical techniques are used to follow the whole crystallization process. The zeolite undergoes amorphous phase reorganization twice before the occurrence of nucleation, crystallization and crystal growth. The zeolite W obtained exhibit nanorods morphology and tend to assemble in parallel forming bulkier bundle-like secondary particles. Lastly, the synthesis of nanocrystalline zeolite W with hierarchical mesoporosity under microwave heating condition was discussed.